HBR guide to getting the right work done. - Harvard Business Review Press (Boston, Mass. : Harvard Business Review Press, 2012)
"In the HBR Guide to Getting the Right Work Done, you'll discover how to focus your time and energy where they will yield the greatest reward. Not only will you end each day knowing you made progress--your improved productivity will also set you apart from the pack. Whether you're a new professional or an experienced one, this guide will help you: Prioritize and stay focused; Work less but accomplish more; Stop bad habits and develop good ones; Break overwhelming projects into manageable pieces; Conquer e-mail overload; Write to-do lists that really work.
Get started -- You can't get it all done -- So what should you do? / by Peter Bregman -- Nine things successful people do differently -- It's not who you are : it's what you do/ by heidi grant halvorson -- Being more productive : an interview with david allen and tony schwartz -- Do you need the right system or the right frame of mind? / by Daniel McGinn -- Prioritize your work -- Get a raise by getting the right work done -- Focus on the work that will bring the greatest reward for your organization and for you / by Peter Bregman -- The worth-your-time test -- Stop wasting time on the wrong work / by Peter Bregman -- Say yes to saying no -- Make it easier to decline projects and invitations / by Alexandra Samuel -- Organize your time -- A practical plan for when you feel overwhelmed -- How to get started when you don't know where to begin / by Peter Bregman -- Stop procrastinating now -- Tips for breaking this bad habit / by Amy Gallo -- Don't let long-term projects become last-minute panic -- What to do when you have "all the time in the world" / by Peter Bregman -- Stop multitasking -- Do just one thing to get many things done / by Peter Bregman -- How to stay focused on what's important -- Stop fighting fires / by Gina Trapani -- To-do lists that work -- The secret is specificity / by Gina Trapani -- How to tackle your to-do list -- Use your calendar / by Peter Bregman -- Reward yourself for doing dreaded tasks -- When crossing items off your list just isn't enough / by Alexandra Samuel -- Delegate effectively -- Management time : who's got the monkey? -- Delegate. delegate. delegate / by William Oncken, Jr., and Donald L. Wass, with commentary by Stephen R. Covey -- Levels of delegation -- Teach them to fish / by Linda A. Hill and Kent Lineback -- Create rituals -- Ritual : how to get important work done -- Make good habits automatic / by Tony Schwartz -- Power through your day in 90-minute cycles -- Work with your body's natural rhythms / by Tony Schwartz -- An 18-minute plan for managing your day -- Frequent check-ins with yourself will keep you on course / by Peter Bregman -- Use a 10-minute diary to stay on track -- The best way to spend the last few minutes of your day / by Teresa Amabile and Steven Kramer -- Renew your energy -- How to accomplish more by doing less -- Take breaks to get more done / by Tony Schwartz -- Manage your energy, not your time -- Time is limited, but your energy is not / by Tony Schwartz and Catherine McCarthy -- Why great performers sleep more -- And how you can, too / by Tony Schwartz -- Take control of your e-mail -- Simplify your e-mail -- Folders will do it / by Gina Trapani -- 8 e-mail overload experiments -- Don't be afraid to be extreme / by Alexandra Samuel -- Maintain your new approach -- Sustaining your productivity system -- You've become productive! : now keep it up / by Alexandra Samuel -- Explore further -- More productivity books to explore : summaries of three popular titles / by Covey, Morgenstern -- Productivity apps and tools -- Tech tools to keep you on track -- Index.
Includes index.
Includes bibliographical references.
Keywords: Time management; Decision making; Facteur temps; Organisation du travail; Decision making; Time management; Zeiteinteilung; Selbstmanagement; Decision making; Time management